1991
DOI: 10.1523/jneurosci.11-02-00420.1991
|View full text |Cite
|
Sign up to set email alerts
|

Factors that determine the magnitude and time course of human H- reflexes in locomotion

Abstract: The soleus H-reflex amplitude is deeply modulated during locomotion in humans (Capaday and Stein, 1986). Moreover, at a constant stimulus intensity, the slope of the relationship between the amplitude of the soleus H-reflex and the background electromyogram (EMG) changes with different locomotor tasks (Capaday and Stein, 1987a). Two further aspects are studied here. First, we recorded the reflex during overlapping speeds of walking (2.0-7.5 km/hr) and running (5-9 km/hr) to determine whether the speed, the mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
117
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 18 publications
7
117
2
Order By: Relevance
“…The size of the H-reflex is essentially dependent on the background EMG of the same muscle (Edamura et al 1991). If reflexes were simply a function of background EMG, one would expect the larger reflexes in CP children to be reflected by a larger background EMG.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The size of the H-reflex is essentially dependent on the background EMG of the same muscle (Edamura et al 1991). If reflexes were simply a function of background EMG, one would expect the larger reflexes in CP children to be reflected by a larger background EMG.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Previous reports suggest that the soleus H-reflex amplitude decreases with increasing walking speeds (17)(18)(19)(20). However, it is not known if the soleus H-reflexes decrease with an increase in walking speed in patients after SCI.…”
Section: Introductionmentioning
confidence: 94%
“…4 in Capaday & Stein, 1987a and Fig. 2 in Edamura et al 1991). This could have potentially forced the linear regressions through the origin and altered the calculations of H-reflex gain (i.e.…”
Section: P Ferris and Othersmentioning
confidence: 99%
“…Previous studies on reflex modulation during human locomotion have concluded that soleus H-reflex gain is greater for walking than for running (Capaday & Stein, 1987a;Edamura et al 1991). Measurements of H-reflex gain are not calculated directly but are inferred based on an operational definition of reflex gain.…”
mentioning
confidence: 99%
See 1 more Smart Citation